EXPORTS AND DEVELOPMENT OF NATIONAL SMALL BUSINESS - Hennings Otoya, Julio Alberto (2011)
Given the difficulties that often presents the Peruvian market, given its limited size for the development of the emerging small industrial company, this could exploit the possibilities offered by the enlarged market of the Andean Community and mostly non tariff barriers for firms Peruvian planning their strategies for business development inroads into neighboring markets, where the similarity with local consumers and the physical proximity would facilitate achieving favorable business results. In this perspective, we analyze the potential impact on export sales growth, and as new international supplier, essential to the development of competitive advantages that allow you to enter a foreign market first, also reviews the administrative changes, production etc. consistent with the new exporter status, and how these repower the new organization. Work, focusing on small business, poured conclusions about the possibilities that are presented to the export units, in order to exploit their potential to pursue development and have an expanded international market.